Social practices a Wittgensteinian approach to human activity and the social - Schatzki, Theodore R. (Cambridge University Press, 1996)
This book addresses key topics in social theory such as the basic structures of social life, the character of human activity, and the nature of individuality. Drawing on the work of Wittgenstein, the author develops an account of social existence that argues that social practices are the fundamental phenomenon in social life. This approach offers insight into the social formation of individuals, surpassing and critiquing the existing practice theories of Bourdieu, Giddens, Lyotard and Oakeshott. In bringing Wittgenstein's work to bear on issues of social theory the book shows the relevance of his work to a body of thought to which it has never been applied. The book will be of particular interest to philosophers of the social sciences, a wide range of social theorists in political science and sociology, as well as some literary theorists
Keywords: Wittgenstein, Ludwig / 1889-1951; Wittgenstein, Ludwig -- 1889-1951; Philosophie; Sozialwissenschaften; Sociology / Philosophy; Social sciences / Philosophy; Sozialphilosophie